The OGTT is highly reproducible in Africans for the diagnosis of diabetes: Implications for treatment and protocol design. (December 2020) - Jagannathan, Ram; DuBose, Christopher W.; Mabundo, Lilian S.; Chung, Stephanie T.; Ha, Joon; Sherman, Arthur; Bergman, Michael; Sumner, Anne E.
Abstract: Whether an OGTT reproducibly detects either type 2 diabetes (T2D) or prediabetes in Africans in unknown. Therefore, 131 Africans had two OGTT. Diagnostic reproducibility for T2D was excellent (κ = 0.84), but only moderate for prediabetes (κ = 0.51). A single OGTT positive for T2D may be sufficient to guide clinical care and inform epidemiologic study design. ClinicalTrials.gov Identifier: NCT00001853.